ChemInform Abstract: Synthesis of 2, 3‐Dihydroquinazolinones and Quinazolin‐4(3H)‐ones Catalyzed by Graphene Oxide Nanosheets in an Aqueous Medium: "On‐Water" Synthesis Accompanied by Carbocatalysis and Selective C—C Bond Cleavage. Issue 28 (June 2016) - Kausar, Nazia; Roy, Indranil; Chattopadhyay, Dipankar; Das, Asish R.
Abstract: The employed catalyst can be easily recycled with a recovery amount of 90% after the fifth run.